'This is my vision': how students depict critiques along with themselves during critiques. (16th December 2020) - McDonald, Jason K.; Michela, Esther
In this article we consider critiques within the design studio as how students press forward into possible forms of the self that are opened up through studio participation. We contrast this with a view of critiques as primarily being a pedagogical or socialising technique under the control of instructors and other critics. We carried out our inquiry using interviews with six studio students, studying how they depict critiques and how they depict themselves when being critiqued. Students' depictions of critiques included their being: a) signal in the noise; b) windows into their critics' character; c) a type of text to be interpreted. Their depictions of themselves included being: a) clear-sighted; b) street-smart; c) creative. We conclude by discussing what these depictions might mean about how instructors/critics can frame critiques in ways that facilitate students using them to take up possibilities that are opened up through studio participation.